Patterns and Predictors of Small Mammal Phylogenetic and Functional Diversity in Contrasting Elevational Gradients in Kenya - Onditi, Kenneth Otieno; Song, Wen-Yu; Li, Xue-You; Chen, Zhong-Zheng; Li, Quan; He, Shui-Wang; Musila, Simon; Kioko, Esther; Jiang, Xue-Long (Frontiers in Ecology and Evolution, 2022)
Mountains of the Afrotropics are global biodiversity hotspots and centres of speciation and endemism, however, very few studies have focused on the phylogenetic and functional dimensions of their small mammals. Here, we investigated the patterns and mechanisms of small mammal phylogenetic and functional diversity and assembly along elevational gradients in Mount Kenya, Africa’ second-highest mountain, and a contrasting low mountain range, Chyulu Hills. We sampled 24 200-meter-interval transects in both sites; 18 in Mt. Kenya [9 each in the windward side, Chogoria, and leeward side, Sirimon] and six in Chyulu. We extracted the mitochondrial Cytochrome b gene to reconstruct a time-calibrated species tree for estimating phylogenetic diversity indices (phylogenetic richness [PD], mean nearest taxon distance [PDMNTD] and nearest taxon index [PDNTI]). A functional trait dataset was compiled from field-recorded measurements and published datasets for estimating functional diversity indices (functional richness [FD], mean nearest taxon distance [FDMNTD] and nearest taxon index [FDNTI]). Several environmental variables representing water-energy availability, environmental-energy availability, primary habitat productivity, and topographic heterogeneity were used to estimate the predictive power of abiotic conditions on diversity variances using generalised linear and generalised additive regression models. The PD and FD peaked around mid-elevations in Mt Kenya, unimodally increased or decreased in Chogoria and Sirimon, and monotonically increased in Chyulu. The divergence and community structure indices — PDMNTD, FDMNTD and PDNTI and FDNTI — were relatively weakly associated with elevation. Overall, the tendency of assemblages to be phylogenetically and functionally less closely related than expected by chance increased with elevation in Mt Kenya but increased in Chyulu. Across indices, the annual precipitation and topographic ruggedness were the strongest predictors in Mt Kenya, evapotranspiration and temperature seasonality were the strongest predictors in Chyulu, while temperature seasonality and terrain ruggedness overlapped as strongest predictors in Chogoria and Sirimon in addition to annual precipitation in the latter and normalized difference vegetation index in the former. The observed contrasting trends in diversity distribution and strongest predictors between elevation gradients are integral to the sustainable management of the high faunal biodiversity in tropical Afromontane ecosystems.